Pigment cell mechanism of postembryonic stripe pattern formation in the Japanese four‐lined snake. (20th November 2015) - Murakami, Arata; Hasegawa, Masami; Kuriyama, Takeo
ABSTRACT: Postembryonic changes in the dermal and epidermal pigment cell architecture of the striped and nonstriped morph of the Japanese four‐lined snake Elaphe quadrivirgata were examined to reveal stripe pattern formation after hatching. The striped and nonstriped morphs were distinguishable at the hatching, suggesting that the basis of stripe pattern was formed during embryonic development. In the striped morph, the color of stripes changed from red‐brown in juveniles to vivid dark‐brown in adults, and density of dermal melanophore increased much more in the stripe than background dorsal scales with growth. This increase in density of dermal melanophore was accompanied not only by the increased epidermal melanophore density but also by the change in vertical structures of dermal melanophore. By contrast, the density of epidermal and dermal melanophore evenly increased over the dorsal scales in the nonstriped morph. Thus, the increased vividness of the stripe pattern after hatching is achieved through localized increase of melanophore density particularly in the stripe region but not over the whole dorsal scales. J. Morphol. 277:196–203, 2016. © 2015 Wiley Periodicals, Inc.